(3GdebOeI aj GdfMhs - (3Ydj Hf aqVGd Hf Ydj Hf ZGdH GdeLGTYj GdbjQhGfj GdaQRObj , CHh GdMSf,J (B479 (3g` s
(3ChdgG (B:s
(3bGd GdTjN gPg ebOeI ai GdfMh JUdM ddeJMaXjf hJdjb HGdeJPGcQjf GdaUd GdChd eYQaI GdcdeI hCMcGegG s
(3BNQgG (B:s
(3hbO MPaJ GdgeRI ai GdNW ef fMh jSFd cPG hcPG hEfeG MPaJ gGgfG dcKQI GdGSJYeGd aGYQa Pdc hHGddg GdJhajb hGdYUeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B165 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B693s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B544s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs